A review on chitosan and its development as pulmonary particulate anti-infective and anti-cancer drug carriers. (15th December 2020) - Rasul, Ruhisy Mohd; Tamilarasi Muniandy, M.; Zakaria, Zabliza; Shah, Kifayatullah; Chee, Chin Fei; Dabbagh, Ali; Rahman, Noorsaadah Abd; Wong, Tin Wui
Graphical abstract: Highlights: Chitosan exhibits mucoadhesive/permeation enhancement/cell targeting attributes. It possesses anti-microbial and anti-cancer properties. Pulmonary chitosan based particulate drug carriers are effective against infection and cancer. Inhalation of nanodrug carrier is promoted by its development as microscale particle. Anti-HCoV chitosan derivatives are new carrier material of interest with therapeutic property. Abstract: Chitosan, as a biodegradable and biocompatible polymer, is characterized by anti-microbial and anti-cancer properties. It lately has received a widespread interest for use as the pulmonary particulate backbone materials of drug carrier for the treatment of infectious disease and cancer. The success of chitosan as pulmonary particulate drug carrier is a critical interplay of their mucoadhesive, permeation enhancement and site/cell-specific attributes. In the case of nanocarriers, various microencapsulation and micro-nano blending systems have been devised to equip them with an appropriate aerodynamic character to enable efficient pulmonary aerosolization and inhalation. The late COVID-19 infection is met with acute respiratory distress syndrome and cancer. Chitosan and its derivatives are found useful in combating HCoV and cancer as a function of their molecular weight, substituent type and its degree of substitution. The interest in chitosan is expected to rise in the next decade from the perspectives of drug delivery in combination with its therapeutic performance.